APPLICATION OF CHEERY INTERACTIVE MULTIMEDIA (MIC) IN INCREASING THEMATIC LEARNING OUTCOMES FOR CLASS IV MIN 1 ROKAN HULU - Fitri Rahmadani; Nurul Huda; Rejeki Rejeki (Indonesian Journal of Basic Education, 2021)
This study aims to determine that the application of cheerful interactive multimedia (MIC) in improving thematic learning outcomes of fourth grade students of MIN 1 Rokan Hulu. This research is also a modified application of ten research steps. Learning outcomes are the acquisition of aspects of implementation in an application of cheerful interactive multimedia (MIC) packaged in power points and combined with various elements of images, animations, audio, video, etc. so as to foster learning motivation. students in class so that students can be active in the application of cheerful interactive multimedia (MIC). The student learning outcomes obtained reached the criteria of 85.3% in the "Highly Effective" category in thematic learning at MIN 1 Rokan Hulu